BREASTFEEDING EXPERIENCES OF WORKING MOTHERS IN VIETNAM - Nguyen Thi Truong Xuan; Nhan Thi Nguyen (Belitung Raya Foundation, Indonesia, 2018)
Background: World Health Organization recommends mothers all over the world should continue breastfeeding up to the age of two years or beyond to achieve optimal health, growth and development for their infants. However, the breastfeeding practices among working mothers have been decreased by the time passed. Objective: to describe the breastfeeding experiences of mothers who returned to work after childbirth. Methods: This study was utilized a qualitative design. Purposive sampling was used to recruit the participant who met the inclusion criteria. Data were collected from 10 semi-structured in-depth interviews. All interviews were audio-recorded and transcribed verbatim. The interview transcriptions were analyzed by using the qualitative content analysis approach. Results: The breastfeeding period of 10 working mothers ranging from 7 to 15 months. Five categories emerged from the data were: 1) Attitude towards breastfeeding, 2) Breastfeeding support during working, 3) Strategic plan for breastfeeding, 4) Psychological distress, and 5) A need for support facilities and resources for breastfeeding during working. Conclusion: This research provided a better understanding of breastfeeding experiences of working mothers in Vietnam. The findings can help nurses and other healthcare professionals in providing anticipatory guidance to mothers who plan to continue breastfeeding after returning to work.